Tingkat Pendapatan, Kecukupan Energi dan Hidden Hunger dengan Status Gizi Balita - Yeni Reska; Arie Krisnasary; Anang Wahyudi (Jurnal Kesehatan, 2018)
Nutritional status is a condition caused by the balance between nutrient intake with nutritional needs for metabolism. Several factors which affect the nutritional status of under five years old children are income, energy intake, micronutrient intake, and infection. This study was to know the relation of income, energy intake and hidden hunger with nutritional status of under five years old children in Jembatan Kecil Health Center in Bengkulu City in 2018. The research was used a cross-sectional design. The sample of research was all of under five years old children in Jembatan Kecil Health Center, and Sixty-seven respondents were obtained by simple random sampling technique. The family income was used questionnaire, the measurement of energy intake and hidden hunger have used a recall 24 hours, and the determination of nutritional status was used the WHO Anthro Standart 2005. The statistical test was used Chi-Square Test. The results showed that most of (61,2%) the family income had a high income, most of (56,7%) child had deficit intake energy and most of the child had deficit Vitamin A (67,2%), Zink (55,3%) and Iodine (74,6%) and almost all (89,6%) of a child had deficit Iron. Almost all of the child had normal nutritional status. The result of bivariate analysis showed that the family income had not a relation with nutritional status of under five years old children, and the energy intake had a significant related to nutritional status index BB/U, p-value 0,029 (p<0,05) and TB/U, p-value 0,018 (p<0,05) of under five years old children. The Hidden Hunger had not related to nutritional status of under five years old children. There was no significant relationship between income, energy intake and hidden hunger with nutritional status of under five years old children. Based on the results of this study is expected to be a consultation or counseling of balanced nutrition and active participation of parents in order to maintain and implements a balanced diet and intake of eating in children.